Characterization and Applications of Nanoparticles Modified in-Flight with Silica or Silica-Organic Coatings - Patrick Post; Lisa Wurlitzer; Wolfgang Maus-Friedrichs; Alfred P. Weber (Nanomaterials, 2018)
Nanoparticles are coated in-flight with a plasma-enhanced chemical vapor deposition (PECVD) process at ambient or elevated temperatures (up to 300 °C). Two silicon precursors, tetraethyl orthosilicate (TEOS) and hexamethyldisiloxane (HMDSO), are used to produce inorganic silica or silica-organic shells on Pt, Au and TiO2 particles. The morphology of the coated particles is examined with transmission electron microscopy (TEM) and the chemical composition is studied with Fourier-transform infrared spectroscopy (FTIR), Energy-dispersive X-ray spectroscopy (EDX) and X-ray photoelectron spectroscopy (XPS). It is found that both the precursor and certain core materials have an influence on the coating composition, while other parameters, such as the precursor concentration, aerosol residence time and temperature, influence the morphology, but hardly the chemical composition. The coated particles are used to demonstrate simple applications, such as the modification of the surface wettability of powders and the improvement or hampering of the photocatalytic activity of titania particles.